Efficient photovoltaic devices based on p-ZnSe/n-CdS core–shell heterojunctions with high open-circuit voltage. Issue 8 (9th February 2017) - Zhang, Xiwei; Mao, Jie; Shao, Zhibin; Diao, Senlin; Hu, Dan; Tang, Zhenjie; Wu, Haihua; Jie, Jiansheng
Abstract : Large band-gap ZnSe nanowires and CdS films are used to construct core–shell heterojunction solar cells with high open circuit voltage and efficiency. Abstract : For solar cells, high open circuit voltage is necessary for their high output voltage. Usually, two methods are used to increase the open circuit voltage: using suitable and matched large band-gap materials and reduction of saturation current. Herein, large band-gap p-type ZnSe nanowires and n-type CdS films are used to construct core–shell p–n heterojunctions with high open circuit voltage. Furthermore, a 4 nm Si3 N4 layer is inserted between the ZnSe core and the CdS shell in order to passivate the interface defects and to reduce recombination and the saturation current. Additionally, a fast annealing process is employed to reduce the series resistance for improved performance. For a typical device, an optimum high open circuit voltage of ∼1.3 V and an energy conversion efficiency of ∼5.27% were achieved for its photovoltaic operation. Moreover, tens of devices were fabricated to demonstrate their stable and consistent performance.